Toxicological evaluation of vegetable oils and biodiesel in soil during the biodegradation process - Tamada, Ivo S. [UNESP]; Montagnolli, Renato N. [UNESP]; Lopes, Paulo R. M. [UNESP]; Bidoia, Ederio Dino [UNESP] (Sociedade Brasileira de Microbiologia, 2012)
Vegetable oils and their derivatives, like biodiesel, are used extensively throughout the world, thus posing an environmental risk when disposed. Toxicity testing using test organisms shows how these residues affect ecosystems. Toxicity tests using earthworms (Eisenia foetida. are widespread because they are a practical resource for analyzing terrestrial organisms. For phytotoxicological analysis, we used seeds of arugula (Eruca sativa and lettuce (Lactuca sativa. to analyze the germination of seeds in contaminated soil samples. The toxicological experiment was conducted with four different periods of biodegradation in soil: zero days, 60 days, 120 days and 180 days. The studied contaminants were soybean oil (new and used) and biodiesel (B100). An evaluation of the germination of both seeds showed an increased toxicity for all contaminants as the biodegradation occurred, biodiesel being the most toxic among the contaminants. on the other hand, for the tests using earthworms, the biodiesel was the only contaminant that proved to be toxic. Therefore, the higher toxicity of the sample containing these hydrocarbons over time can be attributed to the secondary compounds formed by microbial action. Thus, we conclude that the biodegradation in soil of the studied compounds requires longer periods for the sample toxicity to be decreased with the action of microorganisms.
Keywords: bioremediation; toxicity; soybean oil; soil